Longitudinal patterns of physical activity, sedentary behavior, and sleep lifestyle in a representative sample of the Egyptian population 50 years and older: a cross-sectional study - Yasser El Miedany; Israa Qutob; Nada Elkastawy; Hager Abdelaziz; Israa Hanafy; Aseel Elkhouly; Gena Hany; Abdelrahman Maan; Hossam Ghorab; Walaa Elwakil (Egyptian Rheumatology and Rehabilitation, 2025)
Abstract Background In 2018, the World Health Assembly approved a new Global Action Plan on Physical Activity 2018–2023 and endorsed a global target to reduce global levels of physical inactivity in adults and adolescents by 15% by 2030. Egyptian older adults, similar to those in industrial countries, have also reported a lack of physical activity. Earlier data revealed that less than 10% of the older Egyptian population practice regular exercise; of them, the most inactive population were those over the age of 60 years old. A comprehensive understanding of the patterns of physical activity (PA), as well as sedentary and sleep behaviors, would positively impact health professionals and policymakers in adopting national campaigns that promote a healthy, active lifestyle among Egyptian seniors. Results The current study included 679 participants, who were invited to complete a self-reported sedentary, physical activity, and sleep quality self-assessment questionnaire. Our results revealed that only 37% of the participants do not adopt a sedentary lifestyle. Moreover, 55.67% of the participants rarely practice regular PA, and only 30.63% of the participants were physically active. Results of multivariate regression analysis showed that age, female sex, and high BMI were predictors of low PA score. Conclusion The majority of the Egyptian adults and older adults included in this work failed to meet the WHO and the national Egyptian recommendations for physical activity per day. Older adults should do varied multicomponent physical activity at moderate or greater intensity on 3 or more days a week in order to enhance functional capacity, prevent falls, and ensure high-quality sleep. Non-classic approaches, such as social media, can be used to positively change people’s physical activity and diet-related behaviors.